Integrity Testing of a Platform-Pile System Using a Sensor Array and Wavenumber Domain Analysis - Minghui Fu; Meihong Lin (Advances in Civil Engineering)
Appropriate impact and sensor locations must be chosen in pile integrity tests to prevent three-dimensional effects caused by the torsional and flexural modes. The three-dimensional characteristics cause high-frequency interference, especially in bridge and wharf piles. A method is required to minimize the high-frequency interference without reducing the accuracy of the pile integrity test. A multivelocity integrity test method is proposed based on a sensor array and frequency-wavenumber (FK) domain analysis to eliminate high-frequency interference and reduce the errors in the output of integrity tests of platform-pile systems. FK filtering is performed to eliminate the spatial alias frequency and separate the upward and downward wavefield and the vibration modes in an integrity test of a platform-pile system. The optimum sensor location to minimize the influence of interference signals is at the bending plane relative to the impact location. Using a sensor array reduces the influence of the sensor location on the test results and minimizes the requirements for determining the location of the excitation point and sensors in the traditional low-strain integrity testing (LST) method, thereby improving the applicability of this method.